2008
DOI: 10.1007/s00520-008-0513-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of emergency admission and delays in patients with breast cancer

Abstract: Brief diagnostic delays were significantly associated with advanced disease stage and poor survival rates (RR 2.04; CI 95% 1.08-3.82) probably because sicker patients receive prompt medical attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 11 publications
2
30
0
Order By: Relevance
“…Patient's delay represents the time between symptoms' appearance and first consultation with the physician that exceeds 3 months (3,6). Diagnosis delay is the time between seeking medical advice and the date of final diagnosis based on histopathological examination (6).…”
mentioning
confidence: 99%
“…Patient's delay represents the time between symptoms' appearance and first consultation with the physician that exceeds 3 months (3,6). Diagnosis delay is the time between seeking medical advice and the date of final diagnosis based on histopathological examination (6).…”
mentioning
confidence: 99%
“…Similarly, Redondo and colleagues showed a statistically significant association between delays to initiating treatment greater than 30 days and the ductal type, as well as signs or symptoms apart from feeling a nodule in the breast (p= <0.05). 10 The literature has shown an association between skin lesions and discharge from the nipple and a nine-fold increased risk of breast cancer, with a two-fold increased risk when pain is reported. It is important that health professionals identify and communicate possible risks associated with cancer to swiftly refer any patient with suspected disease to ensure continuity of care.…”
Section: Signs and Symptomsmentioning
confidence: 99%
“…7 A meta-analysis of 87 studies showed convincing evidence that women who initiated treatment 3 to 6 months after the appearance of symptoms had a significantly lower five-year survival than those who waited <3 months. 8 Recent studies suggest that care delay does not adequately explain breast cancer survival, 9,10 because sicker patients could receive quicker medical care. 6,7,10 A meta-analysis published in 2013 showed that for every four weeks of delay between surgery and the initiation of chemotherapy, a statistically significant reduction of 15% in overall survival was observed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1] However, the evidence supporting a link between delay in diagnosis and poorer cancer outcome is weak. [14][15][16][17][18][19][20][21][22][23][24][25] The greatest number of studies examining diagnostic delays have been in patients with breast…”
Section: Delays In Diagnosismentioning
confidence: 99%